Turkish adaptation, validity, and reliability study of the Quality of Life Gravidarum (QOL-GRAV) scale - Gamze Ayan; Serap Ejder Apay (BMC Pregnancy and Childbirth)
Abstract Background The study aims to adapt the validity and reliability of the Pregnancy Quality of Life Scale in Turkish society. Methods The study was carried out methodologically between April 2021 and April 2022 at Bayburt State Hospital, the only public hospital operating in the city center of Bayburt. In the study, a total of 355 pregnant women who met the research criteria and volunteered to participate were examined without selecting a sample. Validity and reliability analysis of language and content validity, explanatory and confirmatory factor analysis, and Cronbach- α coefficient were used. Results The factor structure of the Turkish form of the scale was consistent with the original form. As a result of the explanatory appropriate. The internal consistency coefficient was calculated as the total Cronbach-α coefficient of the scale was 0.628 for the first trimester, and 0.628 for the II. trimester 0.727 for trimester, III. Trimester it is 0.698 for a trimester. Conclusion As a result of the validity and reliability study, the Turkish version of the Pregnancy Quality of Life Scale can be used as a valid and reliable measurement tool.